2020
DOI: 10.3390/md18100499
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Low Molecular Weight Sulfate Ulva Polysaccharide and its Protective Effect against IBD in Mice

Abstract: Inflammatory bowel disease (IBD) has been gradually considered a public health challenge worldwide. Sulfated polysaccharides, extracted from seaweed, have been shown to have an anti-inflammatory effect on the disease[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…In the meantime, ulvan is able to recover abnormal levels of oxidative stress and cytokines, and helps to boost the anti-inflammation, as well as anti-oxidation. Li [ 42 ] revealed that ulvan has an alleviative effect on inflammatory bowel disease (IBD) by reducing the DSS-induced disease activity index, colon shortening, and colonic tissue damage. We still need to conduct some targeted bioactive studies using modern technology in order to explore and promote the potential industrial applications of ulvan.…”
Section: Ulvanmentioning
confidence: 99%
“…In the meantime, ulvan is able to recover abnormal levels of oxidative stress and cytokines, and helps to boost the anti-inflammation, as well as anti-oxidation. Li [ 42 ] revealed that ulvan has an alleviative effect on inflammatory bowel disease (IBD) by reducing the DSS-induced disease activity index, colon shortening, and colonic tissue damage. We still need to conduct some targeted bioactive studies using modern technology in order to explore and promote the potential industrial applications of ulvan.…”
Section: Ulvanmentioning
confidence: 99%
“…These heterodisperse sulfated polymers are quite diverse, but generally contain rhamnose, xylose, galactose, and uronic acid. They exhibit lipid-lowering activity [ 13 ], protective effects in irritable bowel syndrome (IBD) models [ 19 ], and antioxidant and antihyperlipidemic effects [ 20 , 21 , 22 ]. A hyperlipidemic rat model showed reductions in non-HDL-cholesterol and increases in HDL-cholesterol and a corresponding improvement in the atherogenic index (log (triglycerides/HDL-cholesterol)) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its biological properties, such as antihyperlipidemic and immunomodulatory, and especially its powerful antioxidant activity, Ulva pertusa is widely used in traditional Chinese medicine as a medication for many human diseases [ 8 ], thus representing a promising natural compound for functional food and drug development [ 9 ]. Despite previous reports [ 10 , 11 ] that have highlighted the activity of Ulva extracts in providing intestinal relief, the knowledge of the multiple molecular pathways with which it acts is still poor.…”
Section: Introductionmentioning
confidence: 99%